Newspaper coverage of agricultural information in Tanzania - Ogessa, Catherine M; Sife, Alfred S (University of Dar es Salaam Library Journal, 2017)
This study examined the coverage of agricultural information in Tanzania ' s newspapers published between 2009 and 2013. Four newspapers €”Mwananchi, Habari Leo, The Guardian and Daily News €”comprising 840 editions were selected for the study. Data were collected using a checklist and analysed using Microsoft excel and SPSS. The study findings show that of the 63,609 news articles in all the four newspaper editions, only 836 (1.3%) articles were on agriculture. The proportion of agricultural news articles published ranged from 0.79 percent in 2010 to 1.92 percent in 2012. Habari Leo had an average of 61.4 agricultural articles followed by Mwananchi with an average of 39.4 articles. The prominence of agricultural information was as low as 4.9 percent in all the newspapers. It is recommended that the government should formulate and institute policies aimed to increase the coverage of developmental topics such as agriculture in the newspapers.